"First, Do No Harm": Have the Health Impacts of Government Bills on Tax Legislation Been Assessed in Finland? - Natassa Aaltonen; Miisa Chydenius; Lauri Kokkinen (Kerman University of Medical Sciences, 2018)
As taxation is one of the key public policy domains influencing population health, and as there is a legal, strategic, and programmatic basis for health impact assessment (HIA) in Finland, we analyzed all 235 government bills on tax legislation over the years 2007-2014 to see whether the health impacts of the tax bills had been assessed. We found that health impacts had been assessed for 13 bills, bills dealing with tobacco, alcohol, confectionery, and energy legislation and that four of these impact assessments included impacts on health inequalities between social classes. Based on our theoretical classification, the health impacts of 40 other tax bills should have been evaluated.